The effect of leg muscle explosiveness, agility, and flexibility on the Padang Club Athletics 100 sprint - Zahra Humairoh; Yendrizal Yendrizal; Arsil Arsil; Nuridin Widya Pranoto; Fiky Zarya (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
This study aims to see the direct or indirect influence of leg muscle explosiveness, agility, and flexibility on the 100-meter sprint speed of Padang club (APC) athletic athletes. This type of research is causal associative quantitative research with path analysis techniques. The population in this study was all 35 Padang club (APC) athletic athletes, 20 adolescent athletes (junior high/high school), 15 and child athletes (elementary school). Sampling using purposive sampling techniques, so the sample in this study was 20 adolescent athletes (junior high/high school). Based on the results of data analysis shows that: (1) There is a direct influence of leg muscle explosive power on 100-meter sprint speed, which is 31.5% (2) There is a direct influence of agility on 100-meter sprint speed of 92.1% (3) There is a direct influence of flexibility on 100-meter sprint speed of 52.1% (4) There is an indirect influence of leg muscle explosive power through flexure on 100-meter sprint speed of 17.7% (5) There is an indirect influence of agility through flex to 100-meter sprint speed by 45.3 % (6) Leg muscle explosive power, agility, and flexibility simultaneously affect the speed of 100-meter sprint in Padang Club Athletics (APC) athletes by 89.2%. It was concluded that the low speed of the 100-meter sprint of Padang Club (APC) athletic athletes was influenced by the explosive power of leg muscles, agility, and flexibility.